Pengaruh Model Pembelajaran Think Pair Share (Tps) Terhadap Peningkatan Hasil Belajar Matematika Di Kelas III SDN Undar Andir 2 - Evita Putri; Tiurlina; Fatihaturosyidah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
This study aims to examine the effect of the Think Pair Share (TPS) learning model on improving student mathematics learning outcomes in grade III SDN Undar Andir 2. This study uses a quantitative approach. This research is an experimental research with the type of Pre-experimental Design in the form of a One-Group Pretest-Posttest Design research design consisting of only one experimental class and linking two variables, namely the independent variable and the dependent variable, the independent variable namely the Think Pair Share learning model and the dependent variable is the result of learning mathematics. The subject of this study was class III with a total of 34 students at SDN Undar Andir 2. The determination of the subject of this study used the Simple Random Sampling technique. The data collection method uses a multiple choice test totaling 9 questions. Based on the findings that have been obtained, the average pretest value data is 35.88 and after the implementation of the Think Pair Share (TPS) learning model there is an increase in the posttest average score of 78.23. The results of the t-test hypothesis obtain a significance value of 0.000 <0.05, which means that Ho is rejected and H1 is accepted. So it can be concluded that in this study there was an influence of the Think Pair Share (TPS) learning model on improving student mathematics learning outcomes in grade III SDN Undar Andir 2.